(untitled) (Research, Society and Development, 2020)
Yacon (Smallanthus sonchifolius) is a tuberous root of Andean origin, considered a functional food, because it contains fructo-oligosaccharides (FOS), and phenolic compounds. The consumption of FOS improves the growth of bifidobacteria in the intestine, gastrointestinal metabolism and stimulates calcium absorption, has antioxidant effect, reduces cholesterol and serum glucose levels. Through this work, the objective was to evaluate the integral use of yacon potato in the elaboration of form loaves. Three loaves were prepared with concentrations of 5%, where the first formulation was composed of the flour of the pulp, the second containing the flour of the bark and the third using the flour of the bark and the pulp of the potato. After processing, the formulations were submitted to microbiological analyzes where they showed negative results for total and fecal coliforms and Salmonella. The results of the preference sorting test and sensory analysis for the attributes texture and flavor showed that there was no significant difference between any of the formulations. Formulation 2 with the shell flour and formulation 1 with the pulp flour, showed good acceptance in relation to the purchase intention, indicating the possibility of commercialization of these products. The results obtained in this study contributed in a significant way to stimulate the integral use of the yacon potato in the elaboration of a differentiated bread, with potential for commercialization and being able to present a high nutritional value.